The living conditions of Polish commercial farmers (participating in FADN) - Kłoczko-Gajewska, Anna; Sulewski, Piotr (Warunki życia polskich rolników towarowych uczestniczących w FADN, 2019)
Monitoring income and property inequalities is important for preparing development policies. The aim of this paper was to assess the living conditions of Polish commercial farmers. The sample was chosen with the use of a layer/random selection procedure and consisted of 600 farms participating in the Farm Accountancy Data Network. The analyses revealed that the farmers find themselves moderately affluent compared to other villagers, and self‑evaluated affluence goes in line with average income per farm. Less than half of commercial farmers make their living exclusively from farming, and the poorest ones mention at least three income sources. Most of the farmers evaluate their housing conditions as good or very good. Only 25% of commercial farmers have access to communal sewage systems, but 17% use home sewage treatment plants. They have relatively easy access (in terms of travel) to important institutions (school, doctor, commune office, extension service)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 64-74
Keywords: living conditions; commercial farmers; Poland; warunki życia; rolnicy towarowi; Polska